Analysis of Three Dimensions of Meaning in the Translation of Religious Verbal Symbols in the Book of Revelation - Erfiani, Ni Made; Putra Yadnya, Ida Bagus; Sudipa, I Nengah; Puspani, Ida Ayu Made (e-Journal of Linguistics; 2016: Vol. 10 No. 2 July)
This present study was intended to reveal that it is so important for a translator to understand meaning when rendering messages from a source text into target text. According to Nida (1964:57), the translator’s low conception of meaning is made up of three dimensions; they are linguistic meaning, referential meaning, and emotive meaning. Such a low conception causes the meaning which is rendered to be distorted, and this negatively affects the target readers especially the common ones, and will become worse when the text which is translated is the one with symbolic language in which the element of the sign, which is referred to as representament , is conventionally related to the object it refers to. The result of analysis of the three dimensions of the meaning of the symbolic phrase the key of David , which is literally translated into kunci Daud , and is dynamically translated into kunci yang dimiliki Daud can cause the dynamic meaning to be distorted. The result of analysis in which the grammatical meaning and the referential meaning of the symbolic phrase the key of David confirm each other is figuratively understood as the authority which is not attached to the entity which is referred to as Daud; rather, it  refers to the authority which is trusted to him. On the other hand, the result of the analysis of emotive meaning, which shows a positive appreciation of the dynamic translation product, implies that it is so important for the translator to understand the symbolic meaning in depth in the process of rendering messages from the source text to the target text.
Keywords: grammatical meaning, referential meaning, emotive meaning